2018
DOI: 10.1007/s11414-018-9634-7
|View full text |Cite
|
Sign up to set email alerts
|

Health Services Use Among Jailed Women with Alcohol Use Disorders

Abstract: Correctional facilities now house unprecedented numbers of women with complex treatment needs. This investigation applied the Behavioral Model for Vulnerable Populations to study 168 jailed women with alcohol use disorders. It described the sample’s predisposing (age, race, victimization), enabling (health insurance), and need (self-reported medical, substance use, and mental health problems) factors and examined associations of these factors with pre-incarceration services utilization. Most participants had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In the criminal justice system, vulnerable populations, such as women (Binswanger et al, 2010; Timko et al, 2019), older adults (Skarupski, Gross, Schrack, Deal, & Eber, 2018), and people with HIV or hepatitis C (Spaulding, Anderson, Khan, Taborda-Vidarte, & Phillips, 2017), are at risk of poor health outcomes. Although these groups have been the focus of numerous research studies, another vulnerable group – military veterans in the criminal justice system – only recently gained attention.…”
Section: Special Populations In the Criminal Justice Systemmentioning
confidence: 99%
“…In the criminal justice system, vulnerable populations, such as women (Binswanger et al, 2010; Timko et al, 2019), older adults (Skarupski, Gross, Schrack, Deal, & Eber, 2018), and people with HIV or hepatitis C (Spaulding, Anderson, Khan, Taborda-Vidarte, & Phillips, 2017), are at risk of poor health outcomes. Although these groups have been the focus of numerous research studies, another vulnerable group – military veterans in the criminal justice system – only recently gained attention.…”
Section: Special Populations In the Criminal Justice Systemmentioning
confidence: 99%
“…Yet a third challenge would be this population possibly having cooccurring opioid or cocaine use disorders for which more intensive treatments such as medications or behavioral interventions would be needed. Indeed, medications are an effective yet underused treatment for AUD (Witkiewitz et al, 2019), and the delivery of SNA interventions may present an opportunity to begin to link women to this and other treatment options, if common barriers to healthcare access and utilization among formerly incarcerated women (Timko et al, 2019) do not interfere.…”
Section: Discussionmentioning
confidence: 99%
“…Women in jail have disproportionately high behavioral health needs, including serious mental illness (SMI) and substance use disorders (SUD), compared to men in jail and to women in the general population (e.g., see Swavola et al, 2016; Timko et al, 2019). Using a broad measure of Serious Psychological Distress (SPD) which captures feelings such as nervousness, hopelessness, or worthlessness, data from the nationally representative National Inmate Survey reveal that a larger percentage of women in jail (32%) than men in jail (26%) met the threshold for past-month SPD (Bronson & Berzofsky, 2017).…”
Section: Behavioral Health Needs Of Women In Jailmentioning
confidence: 99%
“…One 2014 study of nearly 500 women in jails throughout the United States indicate that 53% met 12-month SUD criteria and 84% met lifetime SUD criteria (Lynch et al, 2014). And a recent study on alcohol use disorder among women in jail found high levels of pre-incarceration health service utilization: in the 3 months preceding their jail stay, nearly two-thirds of the 168 women sampled reported an emergency medical visit, roughly one-fifth experienced hospitalization for either medical and/or psychiatric reasons, and about one-fifth visited a counselor for substance abuse treatment (Timko et al, 2019).…”
Section: Behavioral Health Needs Of Women In Jailmentioning
confidence: 99%
See 1 more Smart Citation